Alliance cooperation joint ATM network: exploring the banking sector in Indonesia. (17th July 2019) - Damayanti, Krisna; Setyawardani, Lydia
Abstract : Purpose: This study aims to determine the factors that encourage Indonesian banks to collaborate in the banking networks ATM Prima and ATM Bersama to achieve business efficiencies. Design/methodology/approach: A combination of methods is used to collect both qualitative and quantitative data. Factor analysis and different testing technics are used. The data were obtained through interviews with managers of the banks involved in the two banking networks included in this study. Findings: This research addresses ATM banking from three perspectives: banks that collaborate in ATM networks, banks that are joint ATM providers and banking customers that use ATMs. The results show that the banks in the study are more concerned about cost-effectiveness and cost-efficiencies in both the operational and investment aspects of supporting their ATM infrastructures. ATM providers place more importance on creating the most user-friendly, stable, wide-ranging and continuous system of services by collaborating with other banks in networks that provide ATM services. Customers put more importance on paying the minimum possible administration fees and the availability of specific banking services across a wide area. Research limitations/implications: This research took place over a period of only one year. This limited the depth of the data collected. A longer study using data that cover more than one fiscal year would have generated more detailed information. Practical implications: This study places importance on maximizing cost-efficiencies to keep bank fees low for customers. There are significant investment and operational costs associated with setting up and operating ATMs and of adding and managing additional ATMs. This is particularly so in an era when their use is on the decline owing to the increasing use of electronic banking. Social implications: The social implications of ATM banking refer to the reduced administration fees customers pay as banks incur cost savings from collaborating on infrastructure and services. The availability of ATMs from specific banks could be replaced by one joint ATM machine that is situated in a specific area where electronic banking is not available. Banks' customers tend to move to other banking services, and this means banks could lose a lot of their existing customers unless they can come up with unique services that are both accessible and user-friendly. Originality/value: The originality of this research is that it recommends that some strategies Indonesian banks could use to become more efficient and effective, including forming ATM alliances to maximize efficiency and to achieve a competitive advantage.